Pengawasan Kepemilikan Senjata Jenis Air Gun dan Airsoft Gun di Indonesia: Perspektif Yuridis Normatif - Muhammad Avredo; Shelly Kurniawan (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2023)
The current phenomenon is that there are many cases of the use of air guns and airsoft guns whose true purpose is for sports activities, to be a tool to frighten, terrorize and injure other people. Another thing, the circulation of these types of weapons in the community, deserves attention from law enforcement, because they can cause various incidents. This study uses the normative juridical method, which is to carry out a juridical analysis regarding the ownership of air guns and airsoft guns in the laws and regulations in Indonesia. The results of the research are: the implementation of supervision is carried out by the police; supervision is carried out by means of checking and securing the implementation of permits, and carrying out investigations and investigations in the event of irregularities; also give warnings/sanctions and; as well as revoking licenses and withdrawing weapons. Owners of air guns and airsoft guns are obliged to: store firearms in the warehouse of the Indonesian Shooting Association (Perbakin) or Clubs or in a safe place when not in use; obey the rules; extend the license when the validity period expires; report to the police if the weapon is lost; do not bring weapons to locations that are not permitted; do not use for other purposes; and put an orange tip on the weapon. Suggestions that can be given include: The function of granting licenses in the sale and ownership of air guns and airsoft guns, should be more stringent, especially in terms of conditions that must be met; air guns and airsoft guns must have a manual and explain the dangers if misused. There are criminal sanctions against owners of air guns and airsoft guns who carry, display, and use these weapons in an inappropriate manner.